THEORETICAL AND METHODOLOGICAL FRAMEWORK FOR ASSESSING THE EFFICIENCY OF FARM LAND USE (Development Service Industry Management, 2024)
Under capitalism, the final goal of an entrepreneur or farmer is to make a profit, which is the main source of expanded reproduction. The basis of agricultural production is land - a specific asset that is still not fully included in economic and business turnover. Given the peculiarities of land as a means of production, its capitalization is uneven, and its value is mostly underestimated. It has been identified that the economic efficiency of land resources use should be understood as the overall level of farming on land, characterized by the maximum output at the minimum cost per unit of land area. In this case, the economic effect expresses the costs of manual and capitalized labor, and is also determined by the economic fertility of the soil. It has been shown that economic efficiency does not depend on the form of realization of economic and land relations. In the developed typology of land use efficiency of farms, the basic types of efficiency are economic, environmental, social, technical and technological one. Depending on the sphere of combination of economic interests, the ecological and economic, socio-economic, production and economic, and socio-ecological and economic efficiency of land use can be formed. The latter is at the same time immanent in the rational use of land resources of farms. To assess the level of land use of farms, we have improved the system of indicators that allows us to qualitatively and quantitatively characterize the relevant state of land depending on a particular type of efficiency. This system is based on factor (ecological and landscape condition of land and intensity of land use) and resultant (efficiency of land use as a means of production and an object of management) groups of indicators. In turn, the resultant indicators are divided into natural and cost ones, covering general, partial and supplementary sets of indicators, which characterize the system as a coherent one suitable for strategic planning and analysis. It has been confirmed that the following main methods should be used to assess the efficiency of land resources use by farms: calculation and design method; comparison method; balance method; index method; chain substitution method; factor analysis; functional and cost analysis; normative method; method of expert assessments; graphical method; economic and mathematical methods.
Keywords: land resources; efficiency; land use efficiency; farming; land management; land; economic effect; profit